2021
DOI: 10.2174/1871526520666201116102441
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Evaluation of Bacterial Agents Causing Infection in Children with Acute Tonsillopharyngitis

Abstract: Background: The aim of this study is to evaluate the prevalence of group A beta-hemolytic pharyngitis by assessing the outcome of the culture and the resistance and sensitivity of group A beta hemolytic streptococcus to antibiotics. Methods: This cross-sectional study was conducted on 170 patients, aged 3-15 years, referred to the clinic with complaints of sore throat. Patients’ history was collected and physical examination was performed and were score based on clinical findings. Patients with other underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 41 It is also similar to studies from different countries such as Turkey 7.5%, 42 Indonesia 7.9%, 43 Morocco 9.1%, 44 and Iran 11.8%. 45 However, it was higher than reports from Morocco 6.2%, 46 India 5.5%, 47 Romania 4%, 48 Northern India 2.8%, 49 and Iran 2.5%. 50 On the other hand, it was lower than estimates from Pakistan 25.3%, 51 India 28.4%, 52 Iran 30%, 53 and Yemen 41.5%.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 41 It is also similar to studies from different countries such as Turkey 7.5%, 42 Indonesia 7.9%, 43 Morocco 9.1%, 44 and Iran 11.8%. 45 However, it was higher than reports from Morocco 6.2%, 46 India 5.5%, 47 Romania 4%, 48 Northern India 2.8%, 49 and Iran 2.5%. 50 On the other hand, it was lower than estimates from Pakistan 25.3%, 51 India 28.4%, 52 Iran 30%, 53 and Yemen 41.5%.…”
Section: Discussionmentioning
confidence: 64%
“… 14 , 62 In our study, all the GAS isolates were susceptible to penicillin, which is also reported by several studies worldwide. 30 , 31 , 41 , 45 , 46 Hence, given its narrow spectrum, low cost, and efficacy in preventing strep throat complications such as RHD and PSGN, penicillin remains the drug of choice for treating GAS pharyngitis. 17 Our findings reveal that vancomycin 4.3% and ceftriaxone 13% have reduced susceptibility against GAS causing pharyngitis.…”
Section: Discussionmentioning
confidence: 99%
“…UTI is related with increased health burden among pediatric patients (3). UTI is the most common genitourinary tract disease and the second most common bacterial infection (after respiratory tract infections) in childhood.…”
Section: Introductionmentioning
confidence: 99%